Pengaruh Brand Image Terhadap Keputusan Menggunakan Jasa Klinik Kecantikan dengan Kelompok Referensi Sebagai Variabel Moderasi (Studi Pada Pengguna Jasa Klinik Kecantikan di Surabaya) - Ana Fitria; Sri Setyo Iriani; Sanaji Sanaji (Jurnal Manajemen dan Bisnis Indonesia, 2017)
Consumer perceptions of brands are based on experience and information obtained by consumers. Consumers seek information to evaluate brands before deciding to use the brand. Friends are one of the most effective sources of information in influencing consumer purchasing decisions. This study aims to analyze and discuss the influence of brand image on purchase decision of beauty clinic services that moderated by reference group. This reseach used 220 sample from four beauty clinic services in Surabaya and applied moderating regression analysis to test the research model. The results showed that brand image had a positive and significant influence on the decision to use the beauty clinic services, while reference group con not moderating the influence brand image on the decision to use the beauty clinic services. Keywords : brand image, reference group, use decision